Internet Intermediary Liability under the Internet Governance: Taiwan's Legislative Action - Chih-Liang Yeh; Cheryl Toh Shuet May (International Telecommunications Society (ITS), 2018)
The Internet intermediary has difficulty to monitor all the information on the website. To solve the issue whether the intermediary should be jointly liable for the direct infringer regarding the infringing content, current Copyright Law has rendered an immunity constructed by the notice-and-takedown rule, which does not extend to the other types of online infringement. Such a cooperative obligation has made the intermediary bear heavy burden to monitor online activities. Some countries provide the mechanism of site blocking to protect the rights of right holders; however, such a measure has been challenged by many sectors of community. Recently Taiwan's government announced the proposal of Digital Communications Act attempting to adopt the multi-stakeholders model of Internet Governance to make a smooth communication and to keep the government from intervene the Internet management by administrative measures. It also helps establish the mechanism of value compensation among right holders, users and intermediaries and maintain the neutral role of intermediary to check balances of various interests. This paper attempts to explore the legal development of Internet intermediary liability, to understand the jurisprudential meaning of the concept of Internet governance, and to review whether current legal remedies are enough or not, especially focusing on whether the site blocking measure can be adopted and how to make balances of interests. This paper makes solid suggestions to correct the flaws of the legislation of Digital Communications Act and argues that the Internet Governance focuses not only on the legitimacy of procedural participation but also on the protection of substantial rights, so as to preserve the sound development of entire Internet.
Keywords: 330; Internet Governance; Multi-stakeholders Model; Internet Intermediary Liability; Safe Harbors; Site Blocking; Digital Communications Law